Vitamin D Mitigates Inflammation and Downregulates Importin α3 in Non-Alcoholic Fatty Liver Disease (NAFLD) - Ashok Kujur; S. John Mary; Delinta D; Ajila A; Jesuraj P; Christina C; Gunasekar C J (International Journal of Cheminformatics, 2026)
Non-alcoholic fatty liver disease (NAFLD) affects about one-third of the population in the United States and Western countries, reaching up to 90% among obese individuals and those undergoing bariatric surgery. Characterized by hepatic fat accumulation, NAFLD progresses from simple steatosis to non-alcoholic steatohepatitis (NASH), fibrosis, and, in rare cases, hepatocellular carcinoma. Linked intricately with metabolic syndrome, including diabetes and obesity, NAFLD development involves insulin resistance and hyperinsulinemia. Experimental evidence consistently associates low vitamin D levels with NAFLD severity, independent of age, gender, and BMI. Pro-inflammatory cytokines, such as TNF-α and IL-6, play critical roles in NAFLD, with positive correlations between liver fibrosis and TNF-α levels in NASH patients. The inflammatory cascade involves NF-κB activation, Importin α3, and Importin α4. Vitamin D emerges as a key player, up-regulating the NF-κB inhibitor IкBα and reducing pro-inflammatory activity. Studies in NASH models highlight vitamin D's positive impact on inflammation, fibrosis, and insulin resistance. Recent research underscores calcitriol's role in decreasing Importin α3 expression, influencing NF-κB translocation. This study provides novel insights into calcitriol's effects on Importin α3 and IκBα in HepG-2 cells, unraveling cellular and molecular mechanisms in the intricate interplay between vitamin D and NAFLD pathology.
Keywords: Importin α3; NAFLD; Vitamin D; calcitriol; inflammation; pro-inflammatory cytokines